Amaranth grain processing in a grain roller mill - Shmalko N.; Smirnov S. (Техника и технология пищевых производств)
The article reveals technological aspects of using different types of egg products in mayonnaise production technology. The authors studied the chemical composition of different egg products being used in mayonnaise production technology. The authors studied egg powder, dried egg yolk, enzymatically hydrolyzed dried egg yolk, salted pasteurized liquid egg yolk, egg mixture, and frozen yolk. Based on the obtained data the authors calculated minimum proportions of egg products which are sufficient for producing high quality mayonnaise which complies with the requirements of the standard. The article reveals the results of the research which show the influence of different types of egg products traditionally used in mayonnaise production technology on the organoleptic, physical and chemical properties of the final product such as its consistency, look, stability of undisturbed emulsion, acidity, oxidative deterioration indicators during storage. Study of organoleptic quality indicators of the produced kinds of mayonnaise showed that introduction of egg products in minimum proportions does not lead to the sufficient changes in taste and color of the obtained products. But the samples which include dried egg yolk have heavier and thicker consistency than the samples with whole egg products. The authors developed the recipes and production technology of different types of mayonnaise with mass fraction of fat equal to 67% using different egg products including dried egg yolk modified by phospholipase. That type of egg yolk modification made it possible to guarantee the required viscosity of the product, emulsion stability as well as homogeneous creamy structure. This allowed to use less egg products but did not influence organoleptic properties of the traditional mayonnaise. The authors studied the quality of the produced mayonnaise and checked their organoleptic, physical and chemical properties on compliance with standard requirements.